ARTISTIC EXPRESSION AND TECHNIQUES IN UZBEK WOMEN’S TRADITIONAL CLOTHING - Ochilova Marjona O‘tkir qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the artistic techniques and cultural significance of traditional Uzbek women’s clothing. Focusing on fabrics such as atlas and adras, it examines the methods of weaving, embroidery, zardozi (gold-thread) work, and pattern design used in creating these garments. The study highlights the combination of traditional craftsmanship and modern technology in preserving cultural heritage and enhancing aesthetic expression. The role of these techniques in reflecting regional identity, social status, and ceremonial purposes is also discussed.